Distribution of the lactate/H+ transporter isoforms MCT1 and MCT4 in human skeletal muscle. - Pilegaard, H; Terzis, G.; Halestrap, A; Juel, C (Am J Physiol, 1999)
The profiles of the lactate/H+ transporter isoforms [monocarboxylate transporter isoforms (MCT)] MCT1 and MCT4 (formerly MCT3 of Price, N. T., V. N. Jackson, and A. P. Halestrap. Biochem. J. 329: 321-328, 1998) were studied in the soleus, triceps brachii, and vastus lateralis muscles of six male subjects. The fiber-type compositions of the muscles were evaluated from the occurrence of the myosin heavy chain isoforms, and the fibers were classified as type I, IIA, or IIX. The total content of MCT1 and MCT4 was determined in muscle homogenates by Western blotting, and MCT1 and MCT4 were visualized on cross-sectional muscle sections by immunofluorescence microscopy. The Western blotting revealed a positive, linear relationship between the MCT1 content and the occurrence of type I fibers in the muscle, but no significant relation was found between MCT4 content and fiber type. Moreover, the interindividual variation in MCT4 content was much larger than the interindividual variation in MCT1 content in homogenate samples. The immunofluorescence microscopy showed that within a given muscle section, the MCT4 isoform was clearly more abundant in type II fibers than in type I fibers, whereas only minor differences existed in the occurrence of the MCT1 isoform between type I and II fibers. Together the present results indicate that the content of MCT1 in a muscle varies between different muscles, whereas fiber-type differences in MCT1 content are minor within a given muscle section. In contrast, the content of MCT4 is clearly fiber-type specific but apparently quite similar in various muscles.
Keywords: Adult; Biopsy, Needle; Blotting, Western; Carrier Proteins; Fluorescent Antibody Technique; Humans; Male; Microscopy, Fluorescence; Monocarboxylic Acid Transporters; Muscle Fibers, Skeletal; Muscle, Skeletal; Tissue Distribution